A novel approach for the prediction of thermal distribution in automotive brake rotor - Maleque, Md. Abdul; Adebisi, Adetayo A.; Ahmed, Abu Saleh (2012)
High temperature prediction on the brake rotor-pad interface of automotive brake rotor system was investigated using infrared (IR) thermograph camera and finite element method. Solid brake rotors made from aluminium matrix composite (AMC) and the conventional cast iron were employed in this investigation. The high speed IR camera was connected to a Proton Wira 1.3 brake system rig set up to predict the thermal distribution of the rotors. From the thermographic contour images, it was observed that the material properties of both rotors influenced the maximum temperature reach on the contact surface and the temperature distribution produced. The result obtained from the experimental test was compared with the simulation analysis using ANSYS/LSDYNA FE model, the obtained maximum operating temperature distribution showed a very close outcome. The aluminium composite rotor showed better thermal behaviour during the braking process as far as the maximum temperature and temperature distribution are concerned. In can be concluded from the study that material properties of the rotor brake influences the predictable operational thermal condition during braking.